Strategi Pengembangan Kognitif Anak Usia Dini Melalui Media Kartu Angka Bergambar di Kelompok B Paud Al Rizky Kabupaten Serang - Syarif, Eva Fitriyana; Qalbi, Zahratul; Putera, Rafhi Febryan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Cognitive development has an important role in early childhood development, especially for numeracy skills which are a prerequisite for entering elementary school (SD). This research aims to improve the cognitive abilities of preschool children (5-6 years) at PAUD Al Rizky through the media of picture number cards. The method used was classroom action research (PTK) with two cycles, involving 15 children. Data was collected through observation, interviews and documentation. The results showed a significant increase in the ability to recognize numbers 1-20, number concepts, addition and subtraction. In the first cycle, the percentage of children who were able to recognize numbers 1-20 was 86.6%, number concepts 80%, addition 73.3%, and subtraction 66.6%. In the second cycle, the percentages increased to 100% for numbers, 93.3% for number concepts, 86.6% for addition, and 86.6% for subtraction. The conclusion of this research is that the use of picture number card media is effective in improving the cognitive abilities of young children. It is recommended that teachers use a variety of learning strategies and media to make learning activities fun, and parents are expected to support their children's learning at home.